2010
DOI: 10.1185/03007990903578462
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of therapeutic substitution of drugs for economic reasons: focus on CVD prevention

Abstract: There is a strong rationale for careful management in some patients with cardiovascular disease. Treatment decisions should be transparent and based on strong clinical evidence. If not, drug substitution on economic grounds alone cannot be considered to be in the individual patient's interest and is therefore unethical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
0
29
1
Order By: Relevance
“…For example, a survey of patients in the UK has shown that over 20% reported that they would be very or extremely concerned if their prescription was changed, even with their doctor's approval. Of these, 40% felt that the new drug was less effective than the branded drug and 30% experienced more or different side effects [24]. In another British study, 46% of patients stated that they were dissatisfied when faced with generic substitution [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a survey of patients in the UK has shown that over 20% reported that they would be very or extremely concerned if their prescription was changed, even with their doctor's approval. Of these, 40% felt that the new drug was less effective than the branded drug and 30% experienced more or different side effects [24]. In another British study, 46% of patients stated that they were dissatisfied when faced with generic substitution [25].…”
Section: Discussionmentioning
confidence: 99%
“…The majority [96% (95% CI 91-98)] of participating patients confirmed that they had undergone a kidney transplant more than a year ago. In addition, more than two-thirds were taking more than seven medications [44% (95% CI 36-52) were taking between 7 and 9 medications and 27% (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were taking more than nine medications]. In addition, 74/147 participants [50.34% (95% CI 42-59)] were highly educated (graduated from college, university or postgraduate) and 73/147 participants [49.66% (95% CI 41-58)] were less educated (graduated from secondary school, vocational training or sixth forms) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Cost containment-driven drug substitution is defined as switching to another drug because it is cheaper [1]. It has two forms: generic and therapeutic.…”
Section: Introductionmentioning
confidence: 99%
“…Our observations also support these findings as the effectiveness of the ISS was inferior to the original IS. In other areas (10) 43 (9) 45 (7) 24 (10) of medicine, concerns have also been expressed about the risks associated with switching to non-originator compounds in the absence of adequate clinical testing [34,35]. Because generic and original drugs must demonstrate bioequivalence, one would expect that switching formulations would not be associated with any significant change in everyday clinical practice [36,37].…”
Section: Discussionmentioning
confidence: 99%